Jurnal Kata: on the panoptical eye of self caring in nabakovs the eye : a foucauldian analysis - Taghizadeh, ali, Hajjari, Mohammad javad (Prodi Bahasa Inggris Fak sastra PETRA, 2015)
nabokovs protagonists sufferings, suicide, and final happiness in the eye(1930) can be analyzed through foucaults policy of the care of the self based on which an individual